The Influence Of Civic Knowledge, Civil Skills, And Citizen Involvement On Legal Awareness Among Students - Syafaruddin Syafaruddin; A.M. Fadli Mappisabbi; Nuraziza Aliyah; Andi Riska Andreani Syafaruddin (International Journal of Education and Literature, 2023)
This study examines the influence of civic knowledge, civil skills, and citizen involvement on legal awareness among students. Legal awareness is an essential aspect of citizenship, as it enables individuals to understand their rights, responsibilities, and the legal system governing their society. The research aims to explore how civic knowledge, civil skills, and citizen involvement contribute to the development of legal awareness among students. The study employs a quantitative research design and collects data through a survey questionnaire administered to a sample of students from various educational institutions. The questionnaire includes items that measure the participants' levels of civic knowledge, civil skills, citizen involvement, and legal awareness. Statistical analysis techniques such as correlation and regression analyses are used to examine the relationships between these variables. The findings reveal significant positive associations between civic knowledge, civil skills, citizen involvement, and legal awareness among students. Higher levels of civic knowledge are correlated with increased legal awareness, indicating that a solid understanding of civic principles, institutions, and democratic processes contributes to a better comprehension of legal rights and obligations. Similarly, possessing civil skills, such as critical thinking,problem-solving,and effective communication, positively influences legal awareness. These findings underscore the importance of civic education programs that focus on enhancing civic knowledge, civil skills, and citizen involvement to promote legal awareness among students. Such programs can be integrated into school curricula, extracurricular activities, and community initiatives to foster active citizenship and empower young individuals to be informed and engaged participants in society